Superhydrophobic MOFs decorated on hierarchically micro/nanofibrous membranes for high-performance emulsified oily wastewater separation and cationic dyes adsorption. Issue 2 (17th December 2021) - Ying, Ting; Su, Jiafei; Jiang, Yijing; Ni, Lingyu; Jiang, Xin; Ke, Qinfei; Xu, He
Abstract : A kind of hierarchically micro-patterned porous nanofibrous membrane with superhydrophobic MOFs incorporated (SMOFs@PT) was successfully prepared for the efficient separation of the emulsified oily wastewater and cationic dye adsorption. Abstract : Emulsified oily wastewater from dye production chemical plants is one of the most serious components of wastewater treatment. To develop an effective strategy that can not only efficiently separate the emulsified oily wastewater but also do an effective treatment of cationic dye pollutants in water simultaneously before discharging is still a significant challenge. In this work, a kind of hierarchically micro-patterned porous nanofibrous membrane with superhydrophobic metal–organic frameworks (MOFs) incorporated (SMOFs@PT) was successfully prepared for the efficient separation of the emulsified oily wastewater and cationic dye adsorption. The results exhibited that the fabricated membranes possessed micro-patterned structures, and the elliptical pores on the fibers were evenly distributed, while there were superhydrophobic MOFs (SMOFs) embedded in the fibers. Based on the existence of SMOFs, the hydrophobicity of the as-prepared membranes was steadily improved. Not only that, during the treatment of emulsified oily wastewater, the membranes exhibited a stable and excellent separation efficiency (98% or above), and the flux was significantly improved, which was nearly 2–3 times than that of the membranes without SMOFs. Moreover, due to the electronegativity of the SMOFs and the strong capillary force caused by the highly developed pore structure as well as the high specific surface area of the fibers, the membranes can effectively adsorb the cationic organic dyes (from 20 mg L −1 to 2.5 mg L −1 or even lower in 12 h). All these attractive characteristics demonstrated that the SMOFs@PT have promising application prospects in the treatment of emulsified oily wastewater and cationic dye wastewater.